2018
DOI: 10.22159/ijap.2017.v9s2.29
|View full text |Cite
|
Sign up to set email alerts
|

Eradication Effect of Javanese Turmeric (Curcuma Xanthorrhiza. Roxb.) Extract on the Early Phase of Candida Albicans Biofilm

Abstract: Objectives: To analyze the effect of Javanese turmeric extract on eradicating the initial phase of C. albicans biofilm formation. Methods:A 100 µl of C. albicans suspension 10 −4 was cultured on a 96 -well plate, incubated for 1.5 and 3 h at 37° C and then aspirated and washed by phosphate buffer saline before exposure to 100 µl of 5%, 10%, 15%, 20% 25%, 30%, and 35% Javanese turmeric extract for 24 h. The positive control was 100 µl of nystatin 100,000 IU. Results:The eradication effect of 35% Javanese turmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…The MIC and MFC of Javanese turmeric ethanol extract against planktonic C. albicans in this study were 20% and 35%, respectively. This study had higher MIC and MFC values than a previous study that reported extract MIC and MFC of 10% and 20%, respectively [6]. This difference could be due to the different xanthorrhizol content in the Javanese turmeric extracts used in the studies.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…The MIC and MFC of Javanese turmeric ethanol extract against planktonic C. albicans in this study were 20% and 35%, respectively. This study had higher MIC and MFC values than a previous study that reported extract MIC and MFC of 10% and 20%, respectively [6]. This difference could be due to the different xanthorrhizol content in the Javanese turmeric extracts used in the studies.…”
Section: Discussioncontrasting
confidence: 61%
“…during the proliferation phase (3 hours) [6]. From these two studies, we can see that the more mature the C. albicans biofilm, the higher the extract concentration required to eradicate the biofilm and the weaker the extract's eradication effect.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Medicinal plant's extract from Acacia arabica, Tamarix aphylla L., and Melia azadirachta L. showed evidence of reducing oral biofilm formation and cleaning the well-developed oral biofilm [45]. Medicinal plant from South East Asia, C. xanthorrhiza Roxb., has also been proven through several studies to have eradication and inhibition effects against oral bacteria and candida biofilm [23,[46][47][48][49][50][51][52][53].…”
Section: Current Treatment and Challenges Using Chx And Other Antibac...mentioning
confidence: 99%